2015
DOI: 10.1007/s13762-015-0778-1
|View full text |Cite
|
Sign up to set email alerts
|

Nitrous oxide emissions in a biofilm loaded with different mixtures of concentrated household wastewater

Abstract: Aerobic biofilm systems are increasingly used for household wastewater treatment, but little is known about their potential to emit nitrous oxide in response to different loading conditions. We studied nitrification and nitrous oxide production in a biofilm reactor that was continuously fed with three different mixtures of household wastewater. Higher proportions of blackwater increased nitrification activity, which resulted in enhanced nitrite accumulation and nitrous oxide emissions. Applying a conceptual bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…Todt and D€ orsch (2015) found an emission factor ranging between 0.7% and 8.5% in a pure MBBR system; Kong et al (2013) reported a mean emission factor equal to 2.7% in an MBBR operated with intermittent aeration; Lo et al (2010) found an emission factor equal to 21% of nitrogen load in an IFAS system operated with intermittent aeration. However, Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Todt and D€ orsch (2015) found an emission factor ranging between 0.7% and 8.5% in a pure MBBR system; Kong et al (2013) reported a mean emission factor equal to 2.7% in an MBBR operated with intermittent aeration; Lo et al (2010) found an emission factor equal to 21% of nitrogen load in an IFAS system operated with intermittent aeration. However, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Only a couple of studies have been carried so far (among others Lo et al, 2010;Ma et al, 2015;Todt and D€ orsch, 2015), indicating that significant knowledge gaps still exist. As far as the present authors are aware of, no studies are available on N 2 O emission from IFAS system coupled to MBR and more knowledge is therefore needed.…”
Section: Introductionmentioning
confidence: 99%
“…The latter configuration is usually referred to as MB-MBR (Di Trapani et al, 2014) or IFAS-MBR. Regarding the biofilm influence on N 2 O production, literature shows a very limited knowledge (Todt and D€ orsch, 2015). Indeed, to author's knowledge, there are only few modelling studies that compare the relative effects of the biofilm and the suspended sludge on N and P removal efficiencies and N 2 O emission in a hybrid BNPR system.…”
Section: Introductionmentioning
confidence: 99%
“…The combination of both heterotrophic non-PAOs and PAOs growth inside the anoxic reactors. However, the study of Mannina et al (2017b) Mannina et al (2017b), knowledge on biofilm system is still immature (Todt and D€ orsch, 2015). Therefore, the investigation of different operational conditions for a better understanding of the mechanisms involved in N 2 O production from hybrid systems aimed at nutrient removal is imperative.…”
Section: Introductionmentioning
confidence: 99%
“…Smith (2015) Nitrification and N2O production in a biofilm reactor fed with three different mixtures of household wastewater were studied (Todt et al, 2015). The results showed enhanced nitrite accumulation and N2O emissions with higher proportions of blackwater.…”
Section: Emissions From Wastewater Collection Systemsmentioning
confidence: 99%